A Multiparametric Approach to Study the Preparation Phase of the 2019 M7.1 Ridgecrest (California, United States) Earthquake - De Santis, Angelo; Cianchini, Gianfranco; Marchetti, Dedalo; Piscini, Alessandro; Sabbagh, Dario; Perrone, Loredana; Campuzano, Saioa Arquero; Inan, Sedat (Frontiers in Earth Science, 2020)
The 2019 M7.1 Ridgecrest earthquake was the strongest one in the last 20 years in California (USA). In a multiparametric fashion, we collected data from lithosphere (seismicity), atmosphere (temperature, water vapour, aerosol and methane) and ionosphere (ionospheric parameters from ionosonde, electron density and magnetic field data from satellite). We analysed the data in order to identify possible anomalies that cannot be explained by the typical physics of each domain of study and can be likely attributed to the Lithosphere-Atmosphere-Ionosphere Coupling (LAIC), due to the preparation phase of the Ridgecrest earthquake. The results are encouraging showing a chain of processes that connect the different geo-layers before the earthquake, with the cumulative number of foreshocks and of all other (atmospheric and ionospheric) anomalies both accelerating in the same way as the mainshock is approaching.